2018
DOI: 10.3390/ijms19113467
|View full text |Cite
|
Sign up to set email alerts
|

Maternal β-Cell Adaptations in Pregnancy and Placental Signalling: Implications for Gestational Diabetes

Abstract: Rates of gestational diabetes mellitus (GDM) are on the rise worldwide, and the number of pregnancies impacted by GDM and resulting complications are also increasing. Pregnancy is a period of unique metabolic plasticity, during which mild insulin resistance is a physiological adaptation to prioritize fetal growth. To compensate for this, the pancreatic β-cell utilizes a variety of adaptive mechanisms, including increasing mass, number and insulin-secretory capacity to maintain glucose homeostasis. When insuffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 91 publications
(149 reference statements)
0
102
0
2
Order By: Relevance
“…This is partly attributed to the subtle changes in appetite regulatory mechanisms associated with weight gain and weight retention (Ciampolini et al, 2010;Perry and Wang, 2012). Alterations in leptin (a hormone released from fat cells in adipose tissue altering food intake and control energy expenditure over the long term) signaling also act to increase the risk of diabetes in these women (Moyce and Dolinsky, 2018;Oh et al, 2018). It is therefore of utmost importance to decrease weight retention and to improve glucose control in order to reduce diabetes risk in this population.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly attributed to the subtle changes in appetite regulatory mechanisms associated with weight gain and weight retention (Ciampolini et al, 2010;Perry and Wang, 2012). Alterations in leptin (a hormone released from fat cells in adipose tissue altering food intake and control energy expenditure over the long term) signaling also act to increase the risk of diabetes in these women (Moyce and Dolinsky, 2018;Oh et al, 2018). It is therefore of utmost importance to decrease weight retention and to improve glucose control in order to reduce diabetes risk in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is a period of metabolic plasticity with transient mild insulin resistance as a physiological adaptation to ensure the preferential use of the circulating glucose by the fetus, to prioritize, in this way, fetal growth [1]. During normal pregnancies, maternal sensitivity to insulin is decreased by approximately 50%, which is counteracted by an increase of approximately 250% in maternal insulin production to maintain the euglycemia [2,3].…”
Section: Metabolic Alterations During Pregnancy: Gestational Diabetesmentioning
confidence: 99%
“…GDM is associated with changes, including increased insulin resistance, dyslipidaemia, oxidative stress and inflammatory state (3) . We observed a significant improvement in PPAR-γ and LDLR mRNA expression as well as parameters of glycaemic control, TAG, VLDL-cholesterol, total cholesterol and total cholesterol:HDL-cholesterol ratio.…”
Section: Effects On Glycaemic Control and Lipidsmentioning
confidence: 99%
“…Based on the previous data, an increased risk of adverse perinatal consequences and a wide range of unfavourable long-term outcomes for mother and child are attributed to this condition (2) . Strong evidence suggests a link between peripheral insulin resistance, changes of inflammatory cytokines and biomarkers of oxidative stress in the pathogenesis of GDM (3) . Previous studies also suggested that both pre-existing maternal obesity and gestational diabetes are associated with decreased expression of transcription factors involved in carbohydrate and lipid metabolism such as PPAR, sterol regulatory element-binding protein 1c and increased gene expression levels of adipokines, TNF-α, IL-1β and leptin in adipose tissue (4) .…”
mentioning
confidence: 99%